On the Dominated Convergence Theorem for the Kurzweil–Stieltjes Integral - Henriquez-Miranda, H (John Wiley and Sons Inc, 2023)
This paper is concerned with a version of the Lebesgue dominated convergence theorem (DCT) which has been stated for the Kurzweil–Stieltjes integral of real functions. Our objective in this work is to analyze the extension of this result to include vector functions with values in Banach spaces. We establish that the mentioned convergence theorem for the Kurzweil–Stieltjes integral can be formulated in weaker versions for reflexive and separable Banach spaces, and spaces having the Schur property, nonetheless it is not verified in the general case. © 2023 Wiley-VCH GmbH.